Komunikasi Politik Pasangan Alfedri-Husni (SAH) Dalam Memenangkan Pemilihan Bupati Dan Wakil Bupati Kabupaten Siak Periode 2021-2024 - Sari, Diana; Nasution, Belli; Muchid, Muchid (Jurnal Ilmiah Wahana Pendidikan, 2024)
The political communication carried out by the Alfedri-Husni (SAH) pair in winning the election for Regent and Deputy Regent of Siak Regency can be interpreted as successful. Because this pair was able to defeat their political opponents in the 2020 Siak Regency Regional Head Election (Pilkada), by gaining more than 60 percent of the votes outside the target. In the 2020 regional head elections, there were restrictions on campaign activities due to the Covid-19 outbreak which hit the entire country, thus hampering the political campaign activities of each pair of regional head candidates. A grand campaign is one of the events that cannot be carried out during regional head elections, but this does not make the Alfedri-Husni pair and their team silent, this pair carries out structured political communication.The purpose of this research is to determine the Political Marketing and Political Communication Model used by the Alfedri-Husni (SAH) couple in winning the election for Regent and Deputy Regent of Siak Regency. The research is descriptive qualitative research, and these findings are based on the concept of political marketing with the application of 4 (four) marketing mixes, namely product, promotion, price, placement. With direct interview sources, informants, namely the elected Regent Alfedri and Siak Regency Political Figures. The results of this research show that the political communication model of the Alfedri-Husni (SAH) pair includes Who, Says What, In Which Chanel, To Whom, With what effect, 1. using Siak district political figures as communicators 2. political messages conveyed by "SAH" and “For a More Advanced Siak”. Then 3. using limited face-to-face media, using social media, online media to convey political messages 4. political targets at all levels of Siak district society who have voting rights and young generation of first-time voters 5. The political communication effect of the Alfedri-Husni (SAH) pair is won the regional head election of Siak district